Leadership at the Crossroads of Risk: Bridging Internal and External Factors in Enhancing Risk Management Quality - Ruth Ratih Larasati; Lilik Purwanti; Mohammad Khoiru R (Green Publisher Indonesia, 2025)
This study analyzes the determinants of risk management quality and the role of leadership moderation in the Ministry of Public Works, especially the Directorate General of Highways. These factors are built on attribution theory and transformational leadership by taking into account previous research. This research is a quantitative research using primary data. Data was obtained through the distribution of online questionnaires to risk ownership units (UPR) at the Directorate General of Highways of the Ministry of Public Works and Public Works. The number of samples collected was 162 respondents and processed using PLS-SEM. The results of this study found that organizational culture, competence, regulation, and risk management information systems have a positive effect on the quality of risk management with organizational culture being the variable with the greatest influence. This study also found that leadership plays a role in strengthening the influence of organizational culture, competencies, and risk management information systems on the quality of risk management. The results of this study also have an impact that the presence of leaders is a factor that must be strengthened in compliance with regulations so that the quality of risk management in the Ministry of Public Works can be better. The Ministry of Public Works can focus on increasing the role and leadership in improving compliance with regulations because compliance with regulations has an influence in achieving organizational goals.